Role of ex-situ HfO2 passivation to improve device performance and suppress X-ray-induced degradation characteristics of in-situ Si3N4/AlN/GaN MIS-HEMTs - Dalapati, Pradip (2025)
The role of ex-situ HfO2 passivation in in-situ Si3N4/AlN/GaN-based metal–insulator–semiconductor high-electron-mobility transistors (MIS-HEMTs) to improve the device performance and protect the device from severe degradation under high-energy X-ray irradiation has been investigated. Here, the root cause and mechanism for the degradation have been studied utilizing different material/device characterizations. X-ray photoelectron spectroscopy results suggest that several Si-N bonds in stoichiometric Si3N4 and Hf-O bonds in HfO2 passivation film can be broken under X-ray irradiation, where numerous charges might be trapped easily and deteriorate the interface quality. Furthermore, due to the generation of chemical vacancies under X-ray, a band tail near the edge of valence band maximum in Si3N4 and HfO2 films can be created. The obtained results suggest that MIS-HEMT fabricated with an atomic layer deposited (ALD)-HfO2 (MIS-HEMT B) has relatively greater performance compared to MIS-HEMT fabricated without ex-situ HfO2 (MIS-HEMT A) according to the higher maximum drain current (Idmax), peak transconductance (gmmax) and lower current collapse, denoting the effectiveness of ALD-HfO2 to passivate the surface traps. It is noticed that X-ray irradiation induces numerous negative charges in the dielectric layers and degrades the device performance. Interestingly, after X-ray irradiation, the degradation rates in Idmax, gmmax, and current collapse are significantly lower in MIS-HEMT B compared to MIS-HEMT A, suggesting the potential irradiation hardening mechanism of ALD-HfO2 to protect the MIS-HEMTs from unexpected degradations during X-ray irradiation. Finally, these results emphasize the importance of high-quality dielectric films in MIS-HEMTs to enhance the device performance and safeguard the device under high-energy irradiation, especially in the space environment.